2021
DOI: 10.36001/ijphm.2021.v12i3.2961
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Sensor for Gear Teeth Wear and Damage Detection

Abstract: Health monitoring of mechanical transmission systems is an important area of research. Mechanical transmission systems, especially gear boxes in aircraft, automobiles, and wind turbines etc. account for many of the maintenance costs due to repairs, replacements and downtime. Gear boxes can experience high level of failure due to varied load conditions and harsh environments. Replacing the gear box is quite an expensive process and has significant downtime. Current gear box monitoring involves mainly measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Nevertheless, since the vibration signal processing technique is also a sophisticated technique with numerous signal processing steps, the combination of this technique and the other convolutional neuron network technique or the acoustic emission basically increases the number of steps for reliable results. In the case of the techniques that use sensors and smart materials, the results of [8] confirmed that the effectiveness of the eddy current sensors is undeniable. The attached sensors on the idler gear were able to detect pitting on the face of the metal gear but the accuracy of the result of this study [8] depends considerably on the metallic material of the gear and the density of sensors on the idler gear.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Nevertheless, since the vibration signal processing technique is also a sophisticated technique with numerous signal processing steps, the combination of this technique and the other convolutional neuron network technique or the acoustic emission basically increases the number of steps for reliable results. In the case of the techniques that use sensors and smart materials, the results of [8] confirmed that the effectiveness of the eddy current sensors is undeniable. The attached sensors on the idler gear were able to detect pitting on the face of the metal gear but the accuracy of the result of this study [8] depends considerably on the metallic material of the gear and the density of sensors on the idler gear.…”
Section: Introductionmentioning
confidence: 76%
“…The attached sensors on the idler gear were able to detect pitting on the face of the metal gear but the accuracy of the result of this study [8] depends considerably on the metallic material of the gear and the density of sensors on the idler gear. In comparison to [8], although the application of wireless sensor nodes in [9] can reduce the general dimensions of the gear health monitoring system remarkably, the complexity of the power supply module requires meticulous consideration before the application. Probably, the use of MEMS sensors can be considered a high-accuracy method.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The authors have identified the following examples that can be categorized as sensor-integrating gears: i) Additively manufactured metal spur gear wheel with an integrated accelerometer; [115] ii) case-hardened metal helical gear wheel with hall sensor, accelerometer, temperature sensor, and microphone inside; [116] iii) plastic spur gear wheel with an eddy-current sensor in the teeth; [117] iv) metal spur gear wheel with resistance sensors on the side; [118] v) sensor-integrating metal spur gear with accelerometer on the side. [119,120]…”
Section: Characteristic Parameters On Sensor-integrating Gearsmentioning
confidence: 99%
“…Binder et al, [115] Sridhar & Chana, [117] Peters et al [119,120] use a feather key to fix the gears on the shaft. The feather key concentrates the stress of the interaction between the shaft and the wheel at a certain orbital position.…”
Section: Load-carrying Capacity Of Sensor-integrating Gearsmentioning
confidence: 99%